2016
DOI: 10.1111/jdv.13945
|View full text |Cite
|
Sign up to set email alerts
|

Objective severity does not capture the impact of rosacea, acne scarring and photoaging in patients seeking laser therapy

Abstract: Skin conditions can have a profound impact on patient QOL, which is affected by patients' perception of disease severity and not fully appreciated by dermatologists' own severity assessments. Laser therapy is associated with high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of rosacea on the lives of patients has not been fully appreciated and remains inadequately addressed . There is no short, practical, rosacea‐specific tool to assess disease burden across all rosacea phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The GAGS in our study may have been more congruent with our patient's self-reported acne severity had our patients been more severe as determined by the GAGS. This seems likely given that prior research has shown that a patient's perception of their acne is directly correlated to the impact it has on their quality of life, and objective severity does not always correlate with the impact of the disease experienced by the patient [19,20]. Future research should include subjects with greater acne severity given the impact acne severity has on quality of life, stress, and mental health [13,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%